2010
DOI: 10.1155/2010/291276
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mesiobuccal Canal in Maxillary Molars and Distolingual Canal in Mandibular Molars by Dental CT: A Retrospective Study of 100 Cases

Abstract: Objective. To detect presence of MB2 canal in maxillary molars and distolingual canal in mandibular molars by Dental CT. Material and Methods. A retrospective study of 100 Dental CTs was done. Axial and paraxial images obtained were used to assess the presence of MB2 canal in maxillary molars and distolingual canal in mandibular molars. Results. The youngest patient was of 11 years while the eldest patient was of 77 years. Males were 58 in number and females were 42 in number. MB2 canals were present in 57 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
2
9
0
5
Order By: Relevance
“…In case of disagreement, a joint decision was taken by discussion. A total of seven articles were finally included in the review: one article described the use of dental-CT in vivo [28], and six described the use of CBCT both in in vivo and in ex vivo studies [2227]. Data about study design, population, and device used are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In case of disagreement, a joint decision was taken by discussion. A total of seven articles were finally included in the review: one article described the use of dental-CT in vivo [28], and six described the use of CBCT both in in vivo and in ex vivo studies [2227]. Data about study design, population, and device used are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, Neelakantan et al (1) reported MB 2 in 44.1%; they used another type of CBCT system (3D Accuitomo, Japan). Rathi et al (38) evaluated the frequency of MB 2 by CT and reported its percentage as 57%, while Wasti et al (26) used tooth clearing technique and found the second mesiobuccal frequency in maxillary first molar as 52%. The obtained results of these two studies were lower than this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) as well as spiral CT have been widely used in endodontics in recent years (Stechow et al 2003, Cimilli et al 2005, Nakata et al 2006, Leung 2010, Rathi et al 2010, Singla & Aggarwal 2010, Kaneko et al 2011, Patel et al 2011, Kim 2012. In dentistry, CBCT has been used more routinely than spiral CT due to its higher resolution (Fig.…”
Section: Application Of Computed Tomographymentioning
confidence: 99%